w+76=36w+6

Simple and best practice solution for w+76=36w+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w+76=36w+6 equation:


Simplifying
w + 76 = 36w + 6

Reorder the terms:
76 + w = 36w + 6

Reorder the terms:
76 + w = 6 + 36w

Solving
76 + w = 6 + 36w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-36w' to each side of the equation.
76 + w + -36w = 6 + 36w + -36w

Combine like terms: w + -36w = -35w
76 + -35w = 6 + 36w + -36w

Combine like terms: 36w + -36w = 0
76 + -35w = 6 + 0
76 + -35w = 6

Add '-76' to each side of the equation.
76 + -76 + -35w = 6 + -76

Combine like terms: 76 + -76 = 0
0 + -35w = 6 + -76
-35w = 6 + -76

Combine like terms: 6 + -76 = -70
-35w = -70

Divide each side by '-35'.
w = 2

Simplifying
w = 2

See similar equations:

| 30a+14.8=38(a-1) | | -6x+2x= | | qt=-(4)+50 | | 2x+3y=21 | | 17y+24=-2y+100 | | 3(3x-2)=9 | | 8x+3=3(2x+1)-x+8 | | z=4z-168 | | 3x=22 | | 8q+76=-32+116 | | 4c(2)+21c+27= | | 8q+76=32q+116 | | 7x-4=9X-2 | | 2x+3=38 | | 7x-39=4x | | 14x-22=2x+26 | | 2Y^2+3Y-2= | | 2w^2+w-3=0 | | 8x^2-12=36 | | 11s+28=4s+56 | | 9q+13=22q | | 5u-72=-4u+108 | | 3X^2-2X-8= | | 12-4a=3a | | 6x^2=294 | | t+71=-4t+76 | | WX+WY-2X-ZY= | | 3(2y-1)=8+y | | 9t-85=4t | | 9x-54=36 | | (4x^4+4x^3-5)-(9x^2-7x+2)= | | p+55=6p |

Equations solver categories